Prioritization of factors affecting the safety of sport facilities in Kermanshah Based on AHP - Zarei, Bahieh (2017)
This prioritize the factors affecting the safety of sport facilities based on AHP model is examined. This research strategy in terms of quantity and type AHP, in terms of sectional, both practical and in terms of gathering data is the type of field. The study was based questionnaire measurement elite views were set. In order to test the hypothesis-of a comparison test was used categories together. The Expert Choice software was used in this study. The findings obtained showed that 27 items in 5 categories are involved in determining the safety of sporting venues. On this basis and according to safety experts, sports facilities and sports equipment is the most important component of the Earth's surface. 0.320 is the significance of these items. Management factors weighing 0.268, 0.182 weight room equipment, first aid dressing and platform weighing 0.134 and 0.094 in second weight with the audience. The results showed that the use of safe floors, the use of qualified instructors, the use of appropriate sports flooring, installing warning signs in the hall and regular periodic visits to the salon equipment coefficients 0.070, 0.059, 0.052, 0.049 and 0.047 of the most important items in the factors affecting the safety of the sport.